PROFIL KETERAMPILAN SOSIAL PESERTA DIDIK SMP MUHAMMADIYAH 3 KADUNGORA KABUPATEN GARUT - Nur Puri Handayani; Wikanengsih Wikanengsih; Tita Rosita (IKIP Siliwangi, 2021)
The purpose of this research is to know the description of students' social skills SMP Muhammadiyah 3 Kadungora Kabupaten Garut. The method used is descriptive quantitative research with a social skills scale data collection tool. The results showed that social learning was based on moderate categories. Social skills according to gender shown by the social abilities of women are better than the social skills of male students. The results of social skills research in terms of aspects of social skills found aspects of self-understanding are in there is a low category, whereas communication of social interaction and empathy ability depends on the medium category .Keywords: Social skills, students